Effect of natural zeolite (Clinoptilolite) on the laying hen diet. Its influence on ammonia release through the feces - Lon-Wo, Esmeralda; Acosta, A.; C?rdenas, Mayra (Cuban Journal of Agricultural Science, 2010)
Two hundred and seventy White Leghorn (L33) laying hens were used in a completely random design, divided into two treatments, to evaluate the environmental deodorant effect of zeolite included in the feeding. The treatments consisted of the incorporation of 0 and 3 % natural zeolite in the feed. After the period of diet adaptation (10 d), the feces were collected. The levels of total nitrogen (Nt), ammonia nitrogen (N-NH3), dry matter (DM), and NH3 volatilization degree were determined in the feces. There were (humid and dry basis) higher values of Nt (1.37 and 5.38 vs. 0.74 and 2.91 mg g-1) and N-NH3 (0.31 and 1.19 vs. 0.18 and 0.69 mgg-1) in the feces from the group given zeolite, as well as superior values of dry matter (31.2 %). In the feces sampling dynamics, lower ammonia volatilization was evidenced in the feces from the birds fed on zeolite, because in ten days only 30.6 p.p.m. of NH3 were released to the environment, contrary to 937 p.p.m. released by the control group. These outcomes suggest that it is likable to manipulate laying hen feeding including natural zeolites to reduce environmental contamination and unpleasant smells. Key words: zeolite, feces, nitrogen, ammonia, volatilization.